2012
DOI: 10.1007/s11136-012-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of Greek adolescents: the role of the Mediterranean diet

Abstract: Adherence to the MD positively affects important components of HRQOL in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 27 publications
9
81
2
2
Order By: Relevance
“…In a study of young adults aged 20 24 years in Sweden, Cater et al found that anxiety, posttraumatic stress, and criminal behavior were related to any kind of victimization. They also reported that poly-victimization was related to increased risk of depression, anxiety, suicide ideation, self-harm, criminality, risky alcohol use, and posttraumatic stress (49). In a Danish study of 6200 ninth graders (aged 15-16 years), Helweg-Larsen et al found that exposure to mild or severe physical violence was associated with anxiety and depression.…”
Section: Childhood Adversity and Psychopathologymentioning
confidence: 99%
See 3 more Smart Citations
“…In a study of young adults aged 20 24 years in Sweden, Cater et al found that anxiety, posttraumatic stress, and criminal behavior were related to any kind of victimization. They also reported that poly-victimization was related to increased risk of depression, anxiety, suicide ideation, self-harm, criminality, risky alcohol use, and posttraumatic stress (49). In a Danish study of 6200 ninth graders (aged 15-16 years), Helweg-Larsen et al found that exposure to mild or severe physical violence was associated with anxiety and depression.…”
Section: Childhood Adversity and Psychopathologymentioning
confidence: 99%
“…One aspect poly-victimization has gained broad support in research and has been shown to be significant in several different populations. Poly-victimization occurs when the individual is exposed to several different types of victimization and has been repeatedly confirmed as an important factor (34,43,46,49,83,152). Different types and numbers of types of victimization have been studied, and the main results are robust and reproduced.…”
Section: Childhood Adversity and Poly-victimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, poor nutrition in adolescence affects quality of life and is associated with both short-term and long-term adverse health consequences (13). In this stage, ensure a better nutrition and the promotion of healthy lifestyles that include more physical activity and less sedentary time, is essential to ensure a better health status and prevent the development of nutritional and chronic diseases (14).…”
Section: Introductionmentioning
confidence: 99%